Stochastic Modelling of Spatial Variability of Petrophysical Properties of Zingo Field Niger Delta Basin Nigeria - Agbagie, T. Y.; Ideozu, R. U.; Chiazor, F. I. (European Journal of Applied Sciences, 2023)
This research is focused on the, stochastic modeling of spatial variability of petrophysical properties in reservoir sands in thirteen oil wells of Zingo Field, Niger Delta Basin, Nigeria. Petrophysical properties of the reservoirs sands was generated using well logs, Archie’s equation with Pickett plot and Timur (1968) version of Wyllie and Rose empirical equation. Fault sticks and pillar gridding were used to delineate structural features and generate top surfaces as interpreted horizons on the seismic sections. Results from the stochastic modeling shows that the reservoirs exhibit very good qualities with 17% and 15% volume of shale, 27% and 26% total porosity, 458mD and 565mD permeability for reservoirs C5000 and C6000 respectively. Reservoir C5000 main structures are dipping NE-SW and consists of interpreted major NW-SE fault and other faults trending NE-SW. The research shows that an understanding and properly capturing the reservoir geometry, quality and distribution is important in estimating in place hydrocarbon volumes.